FOXP2 Promotes Tumor Proliferation and Metastasis by Targeting GRP78 in Triple-negative Breast Cancer - Wu, Jiali; Liu, Peng; Tang, Hailin; Shuang, Zeyu; Qiu, Qingsheng; Zhang, Lijuan; Song, Cailu; Liu, Lingrui; Xie, Xiaoming; Xiao, Xiangsheng (Current Cancer Drug Targets, 2018)
Background: FOXP2, a member of the forkhead box P (FOXP) family, has been reported to be important in breast cancer. However, its exact mechanisms and pathways remain unclear. Objective: To investigate the effect of FOXP2 on tumor proliferation and metastasis in triplenegative breast cancer (TNBC) and study its underlying molecular mechanism. Methods: We first used qRT-PCR to detect FOXP2 expression in TNBC cell lines and tissues. Then we conducted cell proliferation assays, colony formation assays, and transwell assays to analyze the effects of FOXP2 expression in TNBC cells. Mouse xenograft model was performed to further confirm the role of FOXP2 in TNBC. Moreover, we used qRT-PCR and Western blot to access the effect of FOXP2 on GRP78 expression and qRT-PCR to analyze GRP78 expression in TNBC tissues. We conducted IHC analysis to detect both FOXP2 and GRP78 expressions in transplanted tumors and used the correlation analysis to further analyze the link between them. Results: FOXP2 was found to be highly expressed in TNBC cell lines and tissues. FOXP2 knockdown attenuated the growth and invasiveness of TNBC in vitro as well as tumor progression and metastasis in vivo. Moreover, FOXP2 knockdown downregulated glucose-regulated protein of molecular mass 78 (GRP78) expression in TNBC cells and transplanted tumors. Correlation analysis showed that GRP78 expression was positively associated with FOXP2 expression in TNBC cells. Conclusion: FOXP2 plays a crucial role in TNBC, partly through modulating GRP78, and could act as a potential target for TNBC treatment.
Keywords: FOXP2